(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the current state of sleep quality and related factors among type 2 diabetes mellitus patients visiting endocrinology outpatient clinics at Hanoi Medical University Hospital in 2025. Subject and methods: A cross-sectional study was conducted through direct interviews with 231 type 2 diabetes mellitus patients. Sleep quality was assessed using the PSQI, with a total score > 5 indicating poor sleep quality. Results: The prevalence of poor sleep quality was 55%, predominantly at mild (62.2%) and moderate (37.8%) levels. Sleep latency (1.50 ± 1.04 points), subjective sleep quality (1.41 ± 0.91 points), and sleep duration (1.35 ± 1.12 points) were the components most significantly affecting overall sleep. Significant statistical associations were observed between poor sleep quality and factors such as female gender OR = 3.00, 95% CI: 1.54-5.83), age ≥ 60 (OR = 1.93, 95% CI: 1.02-3.66) and suboptimal glycemic control (HbA1c ≥ 7%) (OR = 1.96, 95% CI: 1.01-3.80). Conclusion: The prevalence of poor sleep quality among type 2 diabetes mellitus patients at Hanoi Medical University Hospital in 2025 is considerably high. Periodic screening using the PSQI and optimizing glycemic control are essential strategies to enhance patients’ quality of life.